Perilaku Kepemimpinan Pendidikan dalam Meningkatkan Budaya Organisasi Sekolah di Pesantren Anak Sholeh - Tsamrotul Fikriyyah (Journal Islamic Education, 2024)
Educational leadership plays a crucial role in building an organizational culture that supports academic goals and Islamic values within educational institutions. This study aims to analyze the educational leadership behavior in enhancing organizational culture at Pesantren Anak Sholeh (PAS) Baitul Qur'an. The research method employed is a qualitative approach using interview techniques, observation, and document analysis. The findings reveal that the principal at PAS Baitul Qur'an adopts transformational and participative leadership styles, focusing on strengthening the Islamic vision, empowering teachers, and fostering collaboration with various stakeholders. The school's organizational culture is characterized by Islamic norms, collective worship routines, and a spirit of teamwork. However, challenges such as resistance to change and limited resources remain significant. Strategies to address these challenges include continuous training, effective conflict management, and regular evaluations of organizational culture implementation. The study concludes that the educational leadership behavior at PAS Baitul Qur'an is effective in fostering an organizational culture that supports the development of Islamic character and students' academic achievement. Recommendations are provided to enhance leadership programs and improve facilities that support organizational culture.